Contribuição para o estudo dos Rhinotragini (Coleoptera, Cerambycidae).VII. O gênero Ischasioides - Martins, Ubirajara R.; Santos-Silva, Antonio; Clarke, Robin O.S. (Papéis Avulsos de Zoologia, 2012)
Eclipta brasiliensis (Fisher, 1947) is transferred to Ischasioides Tavakilian & Peñaherrera-Leiva, 2003, and synonymized with I. crassitarsis (Gounelle, 1911). Ischasia m. atrocephala Fuchs, 1956 and Ischasia m. nigrovittata Fuchs, 1956, although without nomenclatural status, are confirmed as equal to I. crassitarsis. Ischasioides berkovae sp. nov. is described from Brazil. A key to the species of Ischasioides is provided.